Reconstructing the deposition environment and long-term fate of Chernobyl 137Cs at the floodplain scale through mobile gamma spectrometry. (September 2018) - Varley, Adam; Tyler, Andrew; Bondar, Yuri; Hosseini, Ali; Zabrotski, Viachaslau; Dowdall, Mark
Abstract: Cs-137 is considered to be the most significant anthropogenic contributor to human dose and presents a particularly difficult remediation challenge after a dispersal following nuclear incident. The Chernobyl Nuclear Power Plant meltdown in April 1986 represents the largest nuclear accident in history and released over 80 PBq of 137 Cs into the environment. As a result, much of the land in close proximity to Chernobyl, which includes the Polessie State Radioecology Reserve in Belarus, remains highly contaminated with 137 Cs to such an extent they remain uninhabitable. Whilst there is a broad scale understanding of the depositional patterns within and beyond the exclusion zone, detailed mapping of the distribution is often limited. New developments in mobile gamma spectrometry provide the opportunity to map the fallout of 137 Cs and begin to reconstruct the depositional environment and the long-term behaviour of 137 Cs in the environment. Here, full gamma spectrum analysis using algorithms based on the peak-valley ratio derived from Monte Carlo simulations are used to estimate the total 137 Cs deposition and its depth distribution in the soil. The results revealed a pattern of 137 Cs distribution consistent with the deposition occurring at a time of flooding, which is validated by review of satellite imagery acquired at similar times of the year. The results were also consistent with systematic burial of the fallout 137 Cs by annual flooding events. These results were validated by sediment cores collected along a transect across the flood plain. The true merit of the approach was confirmed by exposing new insights into the spatial distribution and long term fate of 137 Cs across the floodplain. Such systematic patterns of behaviour are likely to be fundamental to the understanding of the radioecological behaviour of 137 Cs whilst also providing a tracer for quantifying the ecological controls on sediment movement and deposition at a landscape scale. Graphical abstract: Interpolated handheld gamma-ray spectrometry estimates for activity (kBq m −2 ) and β (g cm 2 ).Image 1 Highlights: Cs-137 is harmful to human health. Approximatelyone third of the 137 Cs released from Chernobyl was deposited in the Polessie State Radioecology Reserve. Complex post-depositional environment presented in floodplains. High spatial resolution data obtained using handheld gamma-ray spectrometer can infer activity and depth of contamination. Abstract : Complex deposition patterns of 137 Cs have been observed on floodplains providing insight into the role environmental processes play in the spatio-temporal redistribution of contamination.